The Relationship Between Mother's Occupation and the Intensity of Toddlers’ Gadget Use - Putri Naza Rina; Siti Arifah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Background: The use of digital devices among early childhood has increased significantly, which canimpact aspects of child development. This phenomenon is also influenced by various environmentalfactors, including the role and activities of parents in their children's daily lives. Objective: The aimof this study is to determine the relationship between maternal occupation and the intensity of gadgetuse among toddlers in Gatak Village.Method: This was a descriptive correlative study with a cross-sectional approach. The study involved 69 mothers who had children aged 1–3 years and were selectedusing purposive sampling. The demographic data questionnaire was used to evaluate thecharacteristics of children and mothers, while the gadget use was evaluated using the gadget usagequestionnare. Data analysis used the Chi-Square test Result: Statistical tests showed a p-value of 0.019(p < 0.05), indicating a significant relationship between mothers' occupation and the intensity ofgadget use among toddlers in Gatak Village. Conclusion: Mothers who work outside the home tendto have children with higher gadget use intensity compared to stay-at-home mothers.